Modelling hybrid thermal systems for district heating: A pilot project in wood transformation industry. (1st September 2018) - Paredes-Sánchez, José P.; Conde, M.; Gómez, M.A.; Alves, D.
Abstract: The development of modern cities promotes the emergence of metropolitan areas with industrial areas. This situation favours the development of production nuclei of industrial waste, which is susceptible to being energetically used. Biomass of forest origin is particularly interesting due to its importance as an energy resource that mitigates CO2 emissions. The development of energy modelling methodologies is necessary to achieve cleaner production by circular economy in the world. This study aims to improve existing methods and develop new methods to characterise the energy potential of biomass from wood for thermal energy production. The methodology is based on the implementation of a model that calculates waste in terms of quantity, energy and cost while considering techno-economic and environmental restrictions. The study is developed in the Metropolitan Area of Vigo (MAV) for its wood processing industry. MAV is important for the production of manufactured and semi-manufactured products. The results suggest economic and environmental advantages with the installation of hybrid thermal generation systems to supply part of the heat demand using indigenous resources in the MAV. A total of eight district heating systems can be developed with thermal generation systems by Thermal Hybrid Units (THU). Highlights: Bioenergy management from the wood processing industry is presented. The system involves unconventional energy harvesting and conversion system. Waste to energy model by nodes is defined in a modular energy network. The district heating is implemented in an industrial metropolitan area.